Recent Advances in CRISPR/Cas9 Directed Base Editing - Liu, Nan; Zhou, Lifang; Qu, Junyan; Yao, Shaohua (Current Gene Therapy, 2021)
Recently, CRISPR-based techniques have significantly improved our ability to make desired changes and regulations in various genomes. Among them, targeted base editing is one of the most powerful techniques in making precise genomic editing. Base editing enabled the irreversible conversion of a specific single DNA base, from C to T or and from A to G, in desired genomic loci. This technique has important implications in the study of human genetic diseases, considering that many of them resulted from point mutations. More importantly, the high efficiency of these editing tools also provided great promise in clinical applications. In this review, we discuss the recent progress and challenges of base editing tools.
Keywords: human genetic diseases